Reliability in the development and evaluation of measurement instruments in the health field - Alexandre, Neusa Maria Costa (2013)
ABSTRACT The evaluation of interventions and treatments currently seeks to comprise subjective variables, highlighting the importance of the patient’s perspective regarding the disease and treatment effects. These measurements must be reliable and meet basic properties such as validity, reliability, sensitivity and responsiveness, which represent a broad and extensive methodological evaluation repertoire. The objective was to perform a literature review regarding the concept and methods of evaluating the reliability of measurement instruments, through a bibliographic search on the main databases in the health field. After selecting and analyzing the texts, the information was organized, and a presentation was made of the conceptual bases and methods used to evaluate the reliability of those instruments, including stability, equivalence and internal consistency. It is essential to establish reliability to demonstrate the methodological quality of measurement instruments. Furthermore, the other psychometric properties of an instrument must be verified, thus guaranteeing the trustworthiness of the evaluation process. Descriptors: Validation Studies; Psychometrics; Reproducibility of Results; Questionnaires.